In vitro studies of glucose concentrations for Cell viability in normal and cancer cells - MOUNICA RAJU DANTULURI,; ANIMISHA MOKKAPATI,; RADHAKRISHNA NAGUMANTRI,; SATYANARAYANA RENTALA, (International Journal of Pharma and Bio Sciences, 2018)
Cells from multicellular organisms are dependent upon exogenous signals for survival, growth, and proliferation. Tissue homeostasis in multicellular organisms is attained by a balance between the rate of cell proliferation and that of cell death. Glucose is a simple sugar and plays an important role in tissue homeostasis. It is linked to many long-term health problems like heart diseases, pregnancy complications in women, damage to kidneys and diabetic complications. Monitoring cell viability in vitro is critical in many areas of biomedical research. Biomedical researchers incubate cancer cells with chemicals and then assess cell viability to identify potential drugs for further study. It is important to find the relation of glucose with tumor development. It is known that lack of glucose inhibited tumor progression in cell cultures. Keeping these points in mind, we hypothesized that at various concentrations of glucose the cell viability also varies. In this paper the HepG2 (Hepatic Cancer Cells) and MNCs (Mononuclear cells isolated from healthy volunteer) were subjected to different concentrations of glucose at different time intervals. Cell viabilities were assessed on the basis of glucose concentrations using a MTT assay. Our cell viability studies revealed that the glucose concentrations influenced the cell viability, which was evidenced at concentration of 0.1 M glucose the cell viability was maximum (800-900%). The statistical analysis showed the consistency of the results. This indicates that at optimum concentrations of the glucose cell viability was high. Cell viability assessments on the basis of the glucose consumption in the culture medium are suitable for applications of various cancer cell lines and epithelial cell lines.